How sensitive is regional poverty measurement in Latin America to the value of the poverty line? - R. Andrés Casta\~neda; Santiago Garriga; Leonardo Gasparini; Leonardo R. Lucchetti; Daniel Valderrama (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2018)
This paper contributes to the methodological literature on the estimation of international poverty lines for Latin America based on the official poverty lines chosen by the Latin American governments and commonly used in the public debate. The paper exploits a comprehensive data set of 86 up-to-date official extreme and total urban poverty lines across 18 countries in Latin America, as well as the recently updated values of the national purchasing power parity conversion factors from the 2011 International Comparison Program, and a set of harmonized household surveys. By using 3 and 6 US dollars per person a day at 2011 PPP as the extreme and total poverty lines for Latin America, this paper illustrates the sensitiveness of poverty rates to changes of the values of the poverty lines as a result of the recent update of the PPP values, the period of reference, and the relative cost of living across the countries in the region. The poverty lines with the 2011 PPP values lead to an increase in total poverty rates in Latin America when compared to the 2005 PPP values, while they leave the extreme poverty rate unaffected. In general, country-specific poverty rankings remain fairly stable to the values of the poverty lines selected.
Keywords: I3; I32; D6; E31; F01; 330; poverty; poverty lines; purchasing power parity; Latin America